Animated Video Media for Character Education in Elementary Schools: Analysis of Needs and Perceptions of Canva as a Learning Media - Windayani, April Lina Sri; Triyanto, Triyanto; Sudiyanto, Sudiyanto (Universitas Sebelas Maret, 2025)
This study seeks to ascertain perceptions and evaluate the needs of teachers and students on the utilization of Canva-assisted animated video media in Pancasila Education instruction in primary schools, particularly in fostering ideals of honesty. A descriptive quantitative methodology was employed to gather data using closed questionnaires and observations involving three teachers and 43 students from grades II in Boyolali. Data were collected via a closed-ended questionnaire (20 items across five indicators: material suitability, media effectiveness, learning style alignment, honesty fostering potential, and technological accessibility) and structured classroom observations to evaluate traditional practices. Quantitative data were analyzed descriptively using frequency distributions, percentages, means, and standard deviations to quantify perceptions and needs levels. The analysis results indicated that the five primary factors of material compatibility, media effectiveness, learning style, fostering an honest attitude, and technological accessibility exhibited a significant level of necessity, with an overall average of 89.5%. Classroom observations also revealed the inadequacies of traditional approaches in efficiently imparting character values. These findings underscore the imperative for innovative learning media that is contextual, engaging, and aligned with students' learning characteristics. Canva-assisted animated video media is seen as a viable method for enhancing character education that is both pedagogically and technologically pertinent. This study offers a conceptual advancement in value-based digital media and practical insights for educators, media developers, and policymakers on character education in primary schools. Thus, Canva-based animations effectively support the internalization of honesty values in elementary education.